Debate 1: All Childless Women Age 32-34 Should Be Offered Egg Freezing <subtitle>Motion For – Author: Clare Boothroyd; Motion Against – Author: Sujata Kar</subtitle> - Clare Boothroyd; Sujata Kar (Fertility & Reproduction, 2023)
Motion: For NIL Motion: Against In my opinion this is a very radical approach to managing women’s fertility. Women need ethical, scientific, practical, and doable advice from us as fertility consultants. We shall fail in our duties if we do not give them evidence based yet socially and personally relevant information. My points against egg freezing as a universal policy are as follows: 1.False sense of security. This by far is the most important reason. Women cannot and should not consider frozen eggs like an insurance policy, which they can use when and where they need. 2.Ethical reasoning suggests such a policy might put pressure on women affected reproductive autonomy. They must plan themselves when, where, how and with whom they wish to bear a child. 3.Such a policy may bring about socioeconomic disparities in the society as not all will have access or afford the cost of egg freezing. 4.Cost of the procedure, long-term freezing then IVF/ET will be very substantial and will put burden on a young upcoming struggling with career woman. 5.Healthcare resource diversion/allocation will be significant, with so many other more important women’s healthcare issues at hand. 6.Normalizing delayed childbirth by way of egg freezing could have massive changes in the demography of the society, also psychological pressure in women in follow this principle leading to regrets later in life. In the face of these issues, it might be more beneficial to focus on policies that support women to have children when they feel ready–whether that is at a younger or older age—rather than encouraging them to delay childbearing via egg freezing. This could include parental leave policies, affordable childcare, flexible work arrangements, and ensuring access to fertility treatments for those who need them. Not only policy, but research targeting assisted reproductive technologies aimed towards improving IVF success rates, ovarian rejuvenation, stem cell treatment etc. Will go a long way to satisfy reproductive needs of women of all age groups.